Integrasi Pendidikan Karakter - Relijius dan Pembelajaran Tematik dalam Pengajaran Grammar - Ririn Ambarini (Fakultas Bahasa dan Budaya Asing (FBBA), Universitas Muhammadiyah Semarang, 2017)
This research is a research of the integration of characteristic-religious education and thematic learning in teaching Grammar for junior high school students in SMP Al-Fikri Semarang. The integration of characteristic - religious education and thematic learning in the teaching of Grammar of junior high school students begins with the stages of needs analysis which then developed the learning model, validates the contents and constructs the draft of the learning model to the expert, the improvement of the learning model draft including teaching materials, student worksheets and lesson plan. This learning model is expected to be used by English teachers as a reference in improving the English language skills of junior high school students through the theme of character - religious education. The research begins with a preliminary study that is the study of theory and research findings by compiling the draft of learning model.The result of the research is that the significant level of t-table 0.05 is 2,042 while the result of t test is 2.61. The result of t-test is higher than t-table, it means that the hypothesis received is Hi which states that there is significant value of students' Grammar ability after thematic instruction model which is implemented more specifically in the form of religious character education integration in teaching Grammar for junior high school students.